Lemierre Syndrome: Clinical Challenges And The Anticoagulation Dilemma In Adolescent Care - Pereira, Ana I. (2024)
Lemierre syndrome is a rare, life-threatening condition characterized by an acute otorhinolaryngologic infection with septic thrombophlebitis of the internal jugular vein and septic embolism, particularly to the lungs. We describe a case of a previously healthy 15-year-old female patient who initially presents fever and odynophagia but quickly develops neck and pleuritic chest pain. Computed tomography was performed and the radiological findings confirmed the diagnosis of a Lemierre syndrome. She was managed with antibiotics, anticoagulant for three days and symptomatic treatment, with a gradually improving condition. After 17 days of hospitalisation, due to reappearance of pleuritic pain, a new imaging assessment was performed and showed additional septic emboli in the lungs, which prompted the reintroduction of anticoagulant therapy. Awareness of the existence of this syndrome is essential to ensure a radiological evaluation with computed tomography and thus timely diagnosis and treatment.